The relationship between demographic characteristics and the incidence of dysmenorrhea in women of childbearing age at Sihonongan village, Paranginan district, Humbang Hasundutan regency 2022 - Novitarum, Lilis; Derang, Imelda; Sianturi, Ester Mayliana Putri (Institute of Accounting Research and Novation (IARN), 2023)
Every month women will experience menstruation, most women experience dysmenorrhea or menstrual pain during menstruation, women who have an early age of menarche will have an impact on the incidence of dysmenorrhea and women must also maintain nutritional status, therefore women must maintain a good diet. This study aims to determine the relationship between demographic characteristics and the incidence of dysmenorrhea in women of childbearing age at Sihonongan Village, Paranginan District, Humbang Hasundutan Regency 2022. This type of research used a cross sectional design. The sampling technique in this study use purposive sampling, totaling 90 respondents. The instrument used is a demographic characteristics questionnaire and a dysmenorrhea questionnaire. The results showed that the family history is 65.6%, nutritional status show good category 90% and the incidence of dysmenorrhea was 86.7%. Based on the results of the Fisher exact test statistical test, age is not associated with the incidence of dysmenorrhea, the p-value is 0.867 (>0.05), family history is associated with the incidence of dysmenorrhea, the p-value is 0.006 (<0.05), nutritional status is not associated with the incidence of dysmenorrhea obtained p-value 0.343 (> 0.05). It is recommended for women of childbearing age to pay more attention to nutritional status such as consuming fruits and vegetables that are high in vitamins, protein, and carbohydrates and drinking enough water